Rubidium-doped titanium surfaces with modulatory effects on MC3T3-E1 cell response and antibacterial capacity against Staphylococcus aureus. (12th June 2019) - Chen, Manke; Wu, Shusong; Tan, Yanni; Li, Runcheng; Liu, Yong; Huang, Qianli
Abstract: To simultaneously impart excellent biological activity and antibacterial function to titanium-based metal materials, rubidium-doped titanium surfaces were prepared via alkali heat treatment, subsequent hydrothermal treatment and final heat treatment. The alkali heat treatment was employed to fabricate an amorphous sodium titanate hydrogel layer on titanium substrates. Thereafter, rubidium was introduced through the hydrothermal process. After final heat treatment, crystallized rubidium titanate and sodium titanate were obtained on titanium surfaces. The viability of MC3T3-E1 cells was inhibited on rubidium-doped titanium surfaces for short-term (day 1). With prolonged duration, the viability and alkali phosphatase (ALP) activity were comparable for various surfaces with different amounts of rubidium (day 5). With further increased culture duration, the collagen synthesis (day 10) and in vitro mineralization of osteoblasts were found to be significantly enhanced on rubidium-doped titanium surfaces. The Rb-doped Ti surfaces showed antibacterial capacity against Staphylococcus aureus at both 12 and 24 h. The results indicate that doping rubidium into titanium surfaces could simultaneously endow materials with favorable osteogenic and antibacterial capacity.